2022
DOI: 10.3389/fphar.2022.814724
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Pharmacometrics Analysis of Biomarker Distribution Under Treatment With Standard- or Low-Dose Rivaroxaban in Real-World Chinese Patients With Nonvalvular Atrial Fibrillation

Abstract: Background: The rivaroxaban dose regimen for patients with nonvalvular atrial fibrillation (NVAF) is complex in Asia. Given the high interindividual variability and the risk of bleeding caused by rivaroxaban in Asians, the influencing factors and the relationship between outlier biomarkers and bleeding events need exploration.Methods: The integrated pharmacokinetics (PK)/pharmacodynamics (PD) models were characterized based on rich PK/PD data from 304 healthy volunteers and sparse PD [anti-factor Xa activity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 57 publications
0
22
1
Order By: Relevance
“…The estimation of CL/F (4.19 L/h) in Thai DOAC-eligible AF patients was slightly lower than that reported in other ethnicities, including Caucasians (5.58-6.10 L/h) [20,37]. When compared to other Asian populations, the CL/F in this study is comparable to Japanese (4.72-4.73 L/h) [23,24] but lower than Chinese (5.03-7.39 L/h) [33,34,38]. The estimated V/F (37.5 L) was lower than that reported in other studies (40.3-79.7 L) [23,24,33,34,37].…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…The estimation of CL/F (4.19 L/h) in Thai DOAC-eligible AF patients was slightly lower than that reported in other ethnicities, including Caucasians (5.58-6.10 L/h) [20,37]. When compared to other Asian populations, the CL/F in this study is comparable to Japanese (4.72-4.73 L/h) [23,24] but lower than Chinese (5.03-7.39 L/h) [33,34,38]. The estimated V/F (37.5 L) was lower than that reported in other studies (40.3-79.7 L) [23,24,33,34,37].…”
Section: Discussioncontrasting
confidence: 68%
“…The previous integrated PK/PD study of rivaroxaban in Chinese patients suggested that the median peak Anti-Xa level at a dose of 10 mg was within the expected range for patients with CrCL 30-49 mL/min but not at a dose of 15 mg [38]. As a result, dosage modification based on body weight is unnecessary [38]. Results from our simulations confirmed a lower rivaroxaban dose of 10 mg should be appropriate for patients with poor renal function (CrCl of 30-49 mL/min) regardless of body weight.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Pharmacokinetic characteristics may be related to bleeding risks. Rivaroxaban PPK models have been established in many diseases (including acute coronary syndrome (ACS), hip/knee replacement surgery, venous thrombosis, and nonvalvular atrial fibrillation) in previous studies, and some PPK studies have quantitatively evaluated the influence of genetics and body weight on the PK of rivaroxaban 18–21 . However, to date, little is known about PK characteristics regarding the optimal dosage of rivaroxaban in elderly Chinese patients with nonvalvular atrial fibrillation in a real clinical setting, and the relationship between rivaroxaban pharmacokinetics and hemorrhage risk in the population remains ambiguous.…”
mentioning
confidence: 99%